2017
DOI: 10.1108/mip-05-2017-0091
|View full text |Cite
|
Sign up to set email alerts
|

Sport participation from sport events: why it doesn’t happen?

Abstract: Purpose The purpose of this paper is to present and use an event leveraging framework (ELF) to examine processes and challenges when seeking to leverage a sport event to build sport participation. Design/methodology/approach The study used an action research approach for which the researchers served as consultants and facilitators for local sports in the context of the International Children’s Games. Initially three sports were selected, and two sports were guided through the full leveraging process. Prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 18 publications
1
63
0
2
Order By: Relevance
“…One of the few studies that has sought to examine the processes and challenges of leveraging an event was conducted by Taks, Green, Misener, and Chalip (2018). In that study the authors used an action research approach, which is different from the methodology used in the majority of the previous studies.…”
Section: Opportunity Strategic Objectives and Meansmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the few studies that has sought to examine the processes and challenges of leveraging an event was conducted by Taks, Green, Misener, and Chalip (2018). In that study the authors used an action research approach, which is different from the methodology used in the majority of the previous studies.…”
Section: Opportunity Strategic Objectives and Meansmentioning
confidence: 99%
“…In that study the authors used an action research approach, which is different from the methodology used in the majority of the previous studies. Using action research, Taks et al (2018) examined the barriers to leveraging a sport event for sport participation. Specifically, the authors acted as consultants and facilitators to local sport organisations, observed and participated in the attempted leverage process, immediately prior to, during and after the event.…”
Section: Opportunity Strategic Objectives and Meansmentioning
confidence: 99%
See 3 more Smart Citations